Pendidikan Kristiani Berbasis Karakter dan Relevansinya bagi Sekolah Menengah Kejuruan Swasta Armajaya Sindagamanik - Sunggul Simarangkir; Valentina Dwi Kuntari J (REAL DIDACHE: Journal of Christian Education, 2022)
This article discusses character-based Christian education and its relevance for the Armajaya Sindagamanik Private Vocational High School (SMKS). This article uses a qualitative approach with a descriptive method. The Christian students of SMKS Armajaya who are considered as the next generation of the nation as well as the church, are currently trapped in a life that is not pleasing to God, such as smoking, misusing technology during learning, lacking respect for teachers, saying dirty words, and not coming on time. to school and so on. Actually, Christian character should be included in the teachings of God's word, but over time, the character of SMKS Armajaya students is decreasing and not leading to the teachings of God's word anymore, so they don't realize that their character is not good. Thus, character education plays an important role in the personal development of students at SMKS Armajaya. Therefore, in this study, various noble values will be discussed, namely: honesty, virtue, courage, discipline, generosity, tolerance, and responsibility as well as character education which begins with a personal encounter with Jesus Christ.Keywords: character; Christian education; students; SKMS Armajaya Sindagamanik AbstrakArtikel ini membahas tentang pendidikan Kristen berbasis karakter dan relevansinya bagi Sekolah Menengah Kejuruan Swasta (SMKS) Armajaya Sindagamanik. Artikel ini menggunakan pendekatan kualitatif dengan metode deskriptif. Siswa-Siswi Kristen SMKS Armajaya yang dianggap sebagai generasi penerus bangsa sekaligus gereja, saat ini terjebak dalam kehidupan yang tidak berkenan di hadapan Allah, seperti merokok, salah menyalahgunakan teknologi pada saat pembelajaran, kurang rasa menghormati guru, berkata kotor, dan tidak datang tepat waktu ke sekolah, dan lainnya. Karakter Kristen seharusnya diikut sertakan pada ajaran firman Allah, namun seiring perkembangan zaman, karakter siswa-siswi SMKS Armajaya semakin menurun dan bukan mengarah pada ajaran firman Allah lagi, sehingga tidak menyadari bahwa karakter mereka sudah kurang baik. Dengan demikian, pendidikan karakter memegang peranan penting dalam pengembangan pribadi siswa-siswi di SMKS Armajaya. Oleh sebab itu, dalam penelitian ini akan dibahas berbagai nilai-nilai luhur, yakni: kejujuran, kebajikan, keberanian, disiplin, kedermawanan, toleransi, dan tanggung jawab serta pendidikan karakter yang dimulai dengan perjumpaan pribadi dengan Yesus Kristus.Kata kunci: karakter; pendidikan kristiani; siswa-siswi; SKMS Armajaya Sindagamanik